2007
DOI: 10.1111/j.1440-1746.2006.04368.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐session, graded esophageal dilation without fluoroscopy in outpatients with lower esophageal (Schatzki’s) rings: A prospective, long‐term follow‐up study

Abstract: Single-session graded esophageal dilation with large caliber Savary dilators without fluoroscopic guidance can be safely used for the symptomatic relief in patients with lower esophageal (Schatzki's) rings. GERD should be treated if present in order to prevent a symptomatic recurrence of the ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Similar to the findings in the current investigation, Eckardt et al [20] found recurrences unpredictable and unrelated to the initial ring diameter or the presence or absence of reflux esophagitis. Different from the observation that recurrence was unrelated to the type of endoscopic treatment [30], the present investigation showed that patients treated with a large bougie diameter (C52 F) had a tendency for a longer time until symptomatic recurrence. This discrepancy might possibly be explained by differences in completeness and length of follow-up or by differences in the definition of remission.…”
Section: Discussioncontrasting
confidence: 67%
“…Similar to the findings in the current investigation, Eckardt et al [20] found recurrences unpredictable and unrelated to the initial ring diameter or the presence or absence of reflux esophagitis. Different from the observation that recurrence was unrelated to the type of endoscopic treatment [30], the present investigation showed that patients treated with a large bougie diameter (C52 F) had a tendency for a longer time until symptomatic recurrence. This discrepancy might possibly be explained by differences in completeness and length of follow-up or by differences in the definition of remission.…”
Section: Discussioncontrasting
confidence: 67%
“…Gastroesophageal reflux disease (GERD) is believed to contribute to the formation of esophageal rings and has been reported in more than half of patients with Schatzki rings . Supporting the role of GERD is the observation that PPIs have been associated with a decreased likelihood of recurrence, at least among patients with documented GERD . One series, for example, reported a 0% recurrence in dysphagia after dilation at a mean of 43 months in patients who had objective evidence of GERD and who were taking a PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective series have demonstrated that symptom recurrence is common. 3,16,20,22 In an illustrative series of 61 patients who were followed for an average of 6 years, 63% required further dilatation for recurrent dysphagia. 22 Another study evaluated 33 patients after dilatation to ≥50 French.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schatzki’s ring is associated with gastro-oesophageal reflux 39 102 103 and with eosinophilic oesophagitis, even in the absence of other endoscopic oesophageal mucosal abnormalities. 100 102 This may explain why patients with rings and acid reflux (demonstrated by pH monitoring), and also unselected patients with Schatzki’s rings appear to have fewer recurrences after dilatation when receiving PPI therapy.…”
Section: Disease-specific Considerationsmentioning
confidence: 99%